2021
DOI: 10.3390/molecules26206302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin Analogues DMC and EF24 in Combination with the Cytokine TRAIL against Kidney Cancer

Abstract: The natural compound curcumin has been shown to have therapeutic potential against a wide range of diseases such as cancer. Curcumin reduces cell viability of renal cell carcinoma (RCC) cells when combined with TNF-related apoptosis-inducing ligand (TRAIL), a cytokine that specifically targets cancer cells, by helping overcome TRAIL resistance. However, the therapeutic effects of curcumin are limited by its low bioavailability. Similar compounds to curcumin with higher bioavailability, such as demethoxycurcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, primary tumors frequently resist TRAIL-induced apoptosis [88]. Researchers tackled this by combining TRAIL with natural dimethoxycurcumin (DMC) or synthetic (EF24) analogues of CUR [89]. In renal adrenocarcinoma cells, TRAIL combined with DMC or EF24 significantly reduced cell viability (32.73% and 11.39%, respectively), and both analogues hindered cell migration [90].…”
Section: Renal Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…However, primary tumors frequently resist TRAIL-induced apoptosis [88]. Researchers tackled this by combining TRAIL with natural dimethoxycurcumin (DMC) or synthetic (EF24) analogues of CUR [89]. In renal adrenocarcinoma cells, TRAIL combined with DMC or EF24 significantly reduced cell viability (32.73% and 11.39%, respectively), and both analogues hindered cell migration [90].…”
Section: Renal Cell Carcinomamentioning
confidence: 99%
“…Elevated ROS production correlates with increased matrix metalloproteinase (MMP)-2 and -9 expression, promoting cell invasion and metastasis in colorectal cancer [89]. H 2 O 2 /TRAIL-induced death has been observed in TRAIL-resistant cells [91].…”
Section: Renal Cell Carcinomamentioning
confidence: 99%
“…DMC, one of the most important curcuminoids, possesses antitumor activities against various human cancer cells, including leukemia, glioma cells, baller cancer, cervical cancer carcinomas, and kidney tumors [ 120 , 121 , 122 , 123 , 124 ], and is an effective adjuvant. Although few investigations have been conducted to assess the effects of DMC on NSCLC, one study on A549 cells showed that DMC downregulates TP expression and represses the expression of ERCC1.…”
Section: The Impact Of Cur Analogs On Nsclcmentioning
confidence: 99%
“…Research also shows that curcumin has a broad spectrum of antitumor activity, including kidney cancer, prostate cancer, ovarian cancer, and other malignant tumors. Curcumin can inhibit tumor cell survival, proliferation, invasion, migration, and induce apoptosis and autophagy [20][21][22].…”
Section: Introductionmentioning
confidence: 99%